PERAN GURU DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR’AN SISWA DI MTs. AL-AHSAN KOTA BOGOR - Rusma Yuni; Fahmi Irfani; Amran Amran (KOLONI, 2022)
This thesis discusses the teacher's role in improving the quality of students' reading of the Qur'an in MTs. Al-Ahsan Bogor City. The objectives to be achieved are to find out how the teacher's role in improving the quality of students' reading of the Qur'an, to find out the factors that affect the quality of students' reading of the Qur'an and the teacher's strategy to overcome obstacles in improving the quality of students' reading of the Qur'an. This research method used a qualitative method with a descriptive approach, the data obtained in this study are in the form of writing, oral speech, interviews and observations. The results showed that the teacher's role in improving the quality of students' reading of the Qur'an was good, the teacher acted as a guide, motivator and facilitator, not only in the classroom but also in the school environment. The factors that become obstacles in improving the quality of students' reading of the Qur'an are the lack of interest in student learning and the lack of roles from parents. The teacher's strategy to overcome obstacles in improving the quality of students' reading of the Qur'an is by creating a more pleasant learning atmosphere and holding additional learning outside the schedule. Keywords: Teacher's Role, Quality of Al-Qur'an Reading, Students